2011
DOI: 10.1177/1356766710391130
|View full text |Cite
|
Sign up to set email alerts
|

Tourist perceived value in a community-based homestay visit: An investigation into the functional and experiential aspect of value

Abstract: This study analyses the dimensionality of tourist perceived value in a context that is rarely studied, community-based homestay tourism. A survey of 353 tourists to homestay villages was used to examine both functional and experiential aspects of perceived value, and structural equation models were used to verify the validity and reliability of the scales. Tourist perceived value was tested and illustrated through a parsimonious construct with five dimensions: (i) functional value (establishment); (ii) functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
106
1
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(118 citation statements)
references
References 42 publications
6
106
1
5
Order By: Relevance
“…However the findings suggested that Functional value do not have any significant impact on Tourist REVISIT intention. This is again contradicts with previous studies (Jamal, et al, 2011;Denys & Mendes, 2014;Phau, et al, 2014).…”
Section: Discussioncontrasting
confidence: 75%
“…However the findings suggested that Functional value do not have any significant impact on Tourist REVISIT intention. This is again contradicts with previous studies (Jamal, et al, 2011;Denys & Mendes, 2014;Phau, et al, 2014).…”
Section: Discussioncontrasting
confidence: 75%
“…Emotional value associates with extrinsic aspects of value in terms of a product's ability to arouse feelings or affective states, for example certain foods can stimulate feelings of comfort while some consumers are said to have emotional relationships with their possessions (Fournier, 1998). The premise that emotions can contribute to value perceptions is evident both in uni-dimensional (e.g., Zeithaml, 1988) and multi-dimensional value research (e.g., Hume & Mort, 2010;Jamal, Otham, Maheran, & Muhammad, 2011;Mathwick et al, 2001) but is dominant in the latter. In the education context emotional value is realised through the affective states that are aroused in the student while studying their degree, for example their sense of pride and self-achievement in taking their course (LeBlanc & Nguyen, 1999).…”
Section: Typologies Of Valuementioning
confidence: 95%
“…It is selfevident that high value is perceived when a product's benefits are greater than the Studies in Higher Education costs involved in its acquisition. Although earlier research tended to focus on a narrow definition of 'value for money', in which quality is the primary benefit and sacrifice is regarded solely as price (e.g., Dodds, Monroe, and Grewal 1991;Teas and Agarwal 2000), recent reviews by Lin, Sher, and Shih (2005) and Sánchez-Fernández and Iniesta-Bonillo (2007) suggest that value is increasingly more commonly conceptualised by researchers within a multi-dimensional framework that considers all the functional, emotional and psychological benefits and sacrifices of a consumption experience (e.g., Jamal et al 2011;Pihlström and Brush 2008;Williams and Soutar 2009). Consequently, we align with the view that value comprises two components: i.e.…”
Section: Studies In Higher Educationmentioning
confidence: 98%